2023
DOI: 10.1186/s40644-023-00568-5
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for preoperative estimation risk of lateral cervical lymph node metastasis in papillary thyroid carcinoma: a multicenter study

Abstract: Background Lateral lymph node metastasis (LLNM) is frequent in papillary thyroid carcinoma (PTC) and is associated with a poor prognosis. This study aimed to developed a clinical-ultrasound (Clin-US) nomogram to predict LLNM in patients with PTC. Methods In total, 2612 PTC patients from two hospitals (H1: 1732 patients in the training cohort and 578 patients in the internal testing cohort; H2: 302 patients in the external testing cohort) were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Lateral LN metastasis in both groups most frequently involved levels III and IV, which is consistent with previous reports. [19] Zhu et al [27] found that gender, maximum tumor diameter, and lesion location significantly influenced LLNM. Similarly, Feng et al [28] identified tumor size, number, and lesion location as independent predictors of LLNM, while Zhuo et al [29] highlighted gender, tumor size, tumor shape, vascularity of lymph nodes, and lymph node location as independent risk factors for LLNM.…”
Section: Discussionmentioning
confidence: 99%
“…Lateral LN metastasis in both groups most frequently involved levels III and IV, which is consistent with previous reports. [19] Zhu et al [27] found that gender, maximum tumor diameter, and lesion location significantly influenced LLNM. Similarly, Feng et al [28] identified tumor size, number, and lesion location as independent predictors of LLNM, while Zhuo et al [29] highlighted gender, tumor size, tumor shape, vascularity of lymph nodes, and lymph node location as independent risk factors for LLNM.…”
Section: Discussionmentioning
confidence: 99%